Lesser Tarsal Metatarsal Joint Fusion Using Nitinol Staples, Bone Marrow Aspirate Concentrate and a Calcaneal Bone Dowel: A Retrospective Comparative Analysis. Issue 1 (January 2022) - Scott, Jared; Thompson, Jay; Johnson, Mark; Anderson, Michael; Hawkins, Bryan J.
Category: Midfoot/Forefoot; Lesser Toes Introduction/Purpose: Estimates suggest nonunion rates following lesser tarsometatarsal (TMT) fusion are up to 11.4%. Various techniques have been employed to improve fusion rates; however, none have shown significant improvement compared to other techniques. Autologous bone dowels, bone marrow aspirate concentrate (BMAC) and continuous compression devices (CCDs), such as nitinol staples, have each shown promising fusion rates in orthopedic literature. There is limited data that suggests using these techniques in conjunction with one another has been successfully employed in the fusion of lesser TMT joints. The aim of this study was to describe our technique using autologous calcaneal bone graft, CCDs and BMAC for lesser TMT fusion and to investigate whether this method improves fusion rates and decreases time to fusion in comparison to traditional constructs. Methods: All patients undergoing arthrodesis of the lesser (2nd/3rd) TMT joints from January 2015 to January 2020 were identified. Exclusion criteria included inadequate clinical or radiographic follow-up, those with only 1st TMT joint arthrodesis, and those less than 18 years old. Chart review allowed patient demographics, risk factors and surgical approach to be identified. Twenty patients (28 lesser TMT joints) treated with arthrodesis by the senior surgeon met inclusion criteria. These patients were then divided into two groups: 1) novel treatment (Nitinol staple, BMAC and calcaneal dowel) and 2) traditional treatment (compression plate and screw construct). We then assessed for radiographic union, time to union and complications. Results: All lesser TMT joints in the novel treatment arm went on to successful clinical and radiographic fusion. The radiographic union rate of the traditional treatment arm was 92% (P=.08). Overall time to fusion was 56 and 82 days for the novel and traditional constructs respectively (P <.05). All patients, regardless of construct, had returned to full weight bearing and maintained hardware at most recent follow-up (minimum 6 months). Conclusion: Continuous compression devices such as the nitinol staple and use of biologic adjuvants appear to decrease nonunion rates and significantly shorten overall time to fusion in lesser TMT joints. Further investigation towards identifying patient specific factors for nonunion is warranted.